2010
DOI: 10.1121/1.3365248
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic cloaking using layered pentamode materials

Abstract: While receiving less attention in the literature than electromagnetic cloaking, theoretical efforts to define and create acoustic cloaks based upon mimicking coordinate transformations through use of metamaterials is of interest. The present work extends recent analysis of Norris [Proc. R. Soc. London, Ser. A 464, 2411-2434 (2008)] by considering a range of cloaks, from those comprised of fluid layers which are isotropic in bulk moduli with anisotropic density to those having anisotropic bulk moduli and isotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 18 publications
0
36
0
Order By: Relevance
“…In two dimensions or in thin plates, usual anisotropic elastic materials can suffice [4,5,6]. In three dimensions, one either needs materials with anisotropic mass density tensors [3,7,8,9] or pentamode materials [3,10,11,12] to implement the counterpart of invisibility cloaks or other devices. Neither of these materials has been realized experimentally so far.…”
mentioning
confidence: 99%
“…In two dimensions or in thin plates, usual anisotropic elastic materials can suffice [4,5,6]. In three dimensions, one either needs materials with anisotropic mass density tensors [3,7,8,9] or pentamode materials [3,10,11,12] to implement the counterpart of invisibility cloaks or other devices. Neither of these materials has been realized experimentally so far.…”
mentioning
confidence: 99%
“…The key idea that enabled progress in those areas was the combination of coordinate transformations with coordinate-dependent, and often extremely exotic [5,[13][14][15], material properties. Transformation optics [3][4][5]11,16] and transformation acoustics [6-8] offer solutions to some inverse scattering problems [17] by reducing them to an elementary one-for example, scattering off a point object in free space.There is no reason why this conceptual approach cannot be used in other areas of physics [18], and, in fact, it has already been applied to conductive heat transfer [19], linear elastodynamics [5,8,[20][21][22][23][24], surface wave [25], and quantum-mechanical matter wave [26] dynamics. The fundamental requirement for the applicability of this concept is the presence of a medium with sufficiently flexible properties, which enables manipulation of the coefficients in the equations describing the dynamical process.…”
mentioning
confidence: 99%
“…There is no reason why this conceptual approach cannot be used in other areas of physics [18], and, in fact, it has already been applied to conductive heat transfer [19], linear elastodynamics [5,8,[20][21][22][23][24], surface wave [25], and quantum-mechanical matter wave [26] dynamics. The fundamental requirement for the applicability of this concept is the presence of a medium with sufficiently flexible properties, which enables manipulation of the coefficients in the equations describing the dynamical process.…”
mentioning
confidence: 99%
“…7 Scandrett et al demonstrated acoustic cloaks can constructed by using layered pentamode-type fluids. 8 All these theories and experiments demonstrate that the optical and acoustical coordinate transformations can be used to manipulate, restrict, and control the flow of energy, in the form of either EM waves or acoustic waves.…”
Section: Introductionmentioning
confidence: 99%